DON IS A HALF-BLOOD (ABOUT THE SPECIFICS OF THE LYRICAL LANDSCAPE IN O. MANDELSTAM'S POEM “WITH A THIN GILLETTE PLATE...”) - Bella A. Mints (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2024)
Mandelstam's poem "With a thin Gillette plate ..." has rarely been subjected to detailed analysis and still contains riddles, the possibility of variable interpretations. This concerns the subtext, the system of images, the intertextual structure, the poetics of the lyrical landscape. In particular, the important components for understanding this text are the connection with traditional culture, the specifics of the "tree" and "river" figurative codes, the relationship of the landscape with other semantic layers, the forms of the presence of the lyrical subject. The image of the half-blood Don, the main mystery of the poem, is of the particular interest. A consistent analysis of stanzas in a system of different contexts allows us to get closer to understanding the symbolism of the poem.